Предмет: Алгебра,
автор: yua78
Упростите выражение: 3/x-3 - x+15/x^2-9 - 2/x
Ответы
Автор ответа:
0
Автор ответа:
0
3/3-х-х-15/(х-3)*(х+3)-2/х=
3х*(х+3)-х(х-15)-2(х-3)*(х+3)/х*(х-3)*(х+3)=
3х^2+9х-х^2+15х-2(х^2-9)/х*(х^2-9)=
3х^2+9х-х^2+15х-2х^2-18/х^3-9х=
0+24х+18/х^3-9х=
24х+18/х^3-9х
3х*(х+3)-х(х-15)-2(х-3)*(х+3)/х*(х-3)*(х+3)=
3х^2+9х-х^2+15х-2(х^2-9)/х*(х^2-9)=
3х^2+9х-х^2+15х-2х^2-18/х^3-9х=
0+24х+18/х^3-9х=
24х+18/х^3-9х
Похожие вопросы
Предмет: Английский язык,
автор: maga04
Предмет: История,
автор: polina20007
Предмет: Қазақ тiлi,
автор: Ghurber
Предмет: Физика,
автор: GeytronikAnton
Предмет: Литература,
автор: kris5656vk